Strategi Implementasi Kebijakan Penanganan Stunting di Era Efisiensi Anggaran dengan Pendekatan Pentahelix pada Badan Perencanaan Kabupaten Seram Bagian Barat - Sahara, Faiqatul; Tehubijuluw, Zacharias; Elake, Nataniel (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the policy implementation strategies for stunting reduction by the Planning Agency of West Seram Regency within the context of budget constraints, emphasizing a collaborative governance approach based on the Pentahelix model. Five key stakeholders—government, academia, business sector, community, and media—are identified as pillars of collaboration in enhancing policy effectiveness. Employing a qualitative case study approach, data were collected through in-depth interviews, participatory observation, and policy document analysis, and were then thematically analyzed to formulate an implementation model that aligns with the conditions of underdeveloped regions. The findings reveal that despite fiscal limitations, stakeholder synergy can foster effective collaborative mechanisms in program execution, provided it is supported by inclusive leadership, dynamic cross-sectoral coordination, and participatory communication. The novelty of this study lies in the integration of collaborative governance and the Pentahelix model within the realm of public health in fiscally constrained areas, specifically in Eastern Indonesia—a region often underrepresented in public administration scholarship. These findings not only expand the conceptual framework of collaborative governance studies but also propose an efficient and adaptive policy implementation model suited for regions facing complex geographical and social challenges. The study recommends strengthening cross-sectoral collaborative networks as a sustainable strategy for social policy while promoting a more contextual and responsive development of public administration science for disadvantaged regions.